Rapidly (and Successfully) Translating Novel Brain Radiotracers From Animal Research Into Clinical Use - Shaw, Robert C.; Tamagnan, Gilles D.; Tavares, Adriana Alexandre S. (Frontiers in Neuroscience, 2020)
The advent of preclinical research scanners for in vivo imaging of small animals has added confidence into the multi-step decision-making process of radiotracer discovery and development. Furthermore, it has expanded the utility of imaging techniques available to dissect clinical questions, fostering a cyclic interaction between the clinical and the preclinical worlds. Significant efforts from medicinal chemistry have also made available several high-affinity and selective compounds amenable for radiolabelling, that target different receptors, transporters and enzymes in vivo. This substantially increased the range of applications of molecular imaging using positron emission tomography (PET) or single photon emission computed tomography (SPECT). However, the process of developing novel radiotracers for in vivo imaging of the human brain is a multi-step process that has several inherent pitfalls and technical difficulties, which often hampers the successful translation of novel imaging agents from preclinical research into clinical use. In this paper, the process of radiotracer development and its relevance in brain research is discussed; as well as, its pitfalls, technical challenges and future promises. Examples of successful and unsuccessful translation of brain radiotracers will be presented.